Formulation development and pharmacokinetic studies of long acting in situ depot injection of risperidone - Vineet Dubey; Tulsi Ram Saini (Universidade de São Paulo, 2022)
Abstract Risperidone is an atypical antipsychotic drug widely prescribed all over the world due to its clinical advantages. The currently available long acting marketed depot formulation of risperidone is a microsphere based preparation using poly-[lactide-co-glycolide] (PLGA) as drug release barrier. It is however, a cold chain product due to thermal instability of PLGA at room temperature. After beginning the depot injection therapy it is administered every two weeks but associated with another drawback of about 3 weeks lag time due to which its tablets are also administered for three weeks so as to attain and maintain therapeutic drug concentration in the body. The present work attempts to develop a long acting depot delivery system of risperidone for once a month administration based on the combination of sucrose acetate isobutyrate and polycaprolactone dissolved in benzyl benzoate to provide an effective drug release barrier for one month without any lag time and which can be stored at room temperature precluding the requirement of cold supply chain. The developed depot formulation showed a sustained in vitro drug release profile with 88.95% cumulative drug release in 30 days with little burst release. The in vivo pharmacokinetic studies of the developed formulation conducted on rats showed attainment of mean peak plasma drug concentration of 459.7 ng/mL in 3 days with a mean residence time of 31.2 days, terminal half-life of 20.6 days, terminal elimination rate constant of 0.0336 per day, and a good in vitro- in vivo correlation.